Smartphones and Higher Education: Mapping the Field - Cruz-Cárdenas, Jorge (2023)
Smartphones are devices widely used by the global population and are the main means by which people connect to the Internet. Smartphones are also being increasingly used in higher education, which has resulted in the generation of a large amount of academic and scientific literature. To present an ordered picture of this significant body of knowledge, the present study seeks to carry out a bibliometric analysis of the academic and scientific literature on smartphones and higher education. For this purpose, the present study uses the Scopus database from which 2,453 articles were selected. A descriptive analysis of this body of documents allows us to observe a rapid growth rate in the number of documents published annually. Additionally, it is possible to establish that the most research on the topic has been carried out in developed and emerging countries. An analysis of the co-occurrence of terms makes it possible to define three research areas: 1) technology and the applications of smartphones in higher education, 2) administrative and pedagogical considerations in the use of smartphones in higher education, and 3) negative effects of smartphone use on students. An analysis of the evolution of research priorities shows a shift of interest from a focus on smartphone technology and its applications to a focus on the negative impacts of the use of these devices and their prevention. The present study ends by presenting the most relevant conclusions and the implications of the findings for future studies.